A 10-Year Prospective Evaluation of Balloon Tube Tamponade and Emergency Injection Sclerotherapy for Actively Bleeding Oesophageal Varices. Issue 3 (1989) - Kahn, D.; Bornman, P. C.; Terblanche, J.
Abstract : During a 10 year study period 234 patients were admitted on 371 occasions with a total of 566 acute variceal bleeding episodes. Of these, 173 patients had 343 variceal bleeds which required balloon tamponade to achieve initial control of bleeding during 229 admissions and were then referred for emergency injection sclerotherapy. Sixty-eight percent of these patients had alcoholic cirrhosis and 42% were poor risk Grade C patients. Injection sclerotherapy was performed initially using the rigid Negus oesophagoscope under general anaesthesia and later using the fibreoptic endoscope under light sedation. Definitive control of variceal bleeding was achieved with sclerotherapy during 197 hospital admissions (92%). Of the 17 failures of emergency sclerotherapy, 4 patients died from uncontrolled bleeding and 13 patients underwent major surgical intervention. Definitive control of variceal bleeding was achieved with a single injection treatment in 138 hospital admissions (70%). Complications were mostly of a minor nature and occurred at a rate of 6% per injection treatment. The overall hospital admission mortality was 36%. The majority of patients died due to liver failure. The mortality in patients who required 4 injection treatments to control variceal bleeding was 71%. Injection sclerotherapy is proposed as the emergency treatment of choice for patients whose variceal bleeding continues or recurs after initial conservative management. Patients whose variceal bleeding is not controlled by 2 injection treatments require more major emergency surgery.